Comparative study of quality control parameters of different brands of oral montelikast tablets available in Bangladesh - Sarkar, Chandan (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015